Effect of Smoking on Periodontal Health: Awareness among Azra Naheed Dental College Patients - Marryam Riaz, Rahmah Kashif, Ahmed Mujtaba, Sara Mukhtar, Sohaib Shujaat, Easha Tahir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Smoking is one of the most preventable causes of premature mortality around the globe. In addition to causing unattractive tooth staining, periodontal disease, bad breath, wounds impaired healing, and precancerous conditions, smoking is also detrimental to oral health. The present study aimed to determine the effect of smoking on periodontal health and to identify the level of awareness among smokers about the effects of smoking on their oral health. Methods: A cross-sectional study was carried out on 200 participants in Azra Naheed Dental College (ANDC), Lahore from January 2022 to September 2022. This self-administrated questionnaire survey was used to determine sociodemographic characteristics, smoking cessation programs and individuals' willingness to quit smoking, as well as awareness of oral health affected by smoking. Dental patients aged ≥19 were enrolled. The questionnaires asked about the demographics of participants, their awareness regarding smoking effects on oral conditions, including staining of teeth, oral cancer, delayed wound healing, gum disease, and dental implants. Results: Of the total 200 participants, there were 144 (72%) male and 56 (28%) females. The overall mean age was 35.8±14.1 years. Age-wise distribution of patients was as follows: 138 (69%) in 19-40 years, 51 (25.5%) in 41-60 years, 6 (3%) in 61-80 years, and 5 (2.5%) >80 years. About 57 (28.5%) had past medical history, out of which hypertension (HTN) was the most prevalent medical history 32 (16%) followed by combined hypertension and diabetes cases 13 (6.5%), diabetes 5 (2.5%), asthma 4 (2%), and vocal cord surgery 3 (1.5%). Regarding Dental history, the incidence of extraction and scaling, scaling, filling, extraction, extraction and filling, scaling extraction and filling, restoration, Root canal treatment (RCT), restoration and RCT, denture, artificial teeth, and capping were 21 (10.5%), 28 (14%), 15 (7.5%), 15 (7.5%), 12 (6%), 6 (3%), 1 (0.5%), 1 (0.5%), 1 (0.5%), 2 (1%), and 2 (1%) respectively. About 82 (41%) participants were smokers among total participants. The incidence of toothless, staining, halitosis, bad taste, effect on gums, delay in healing, tenderness, pain cured, bleeding gums, loose tooth, prostho work, and bad experience were 83 (41.5%), 151 (75.5%), 161 (80.5%), 75 (37.5%), 101 (50.5%), 63 (31.5%), 83 (41.5%), 113 (56.5%), 101 (50.5%), 65 (32.5%), 39 (19.5%), and 23 (11.5%) respectively. Conclusion: The present study concluded that only 8% of respondents knew that smoking is associated with periodontal diseases, illustrating the lack of awareness of patients regarding the link between smoking and periodontal diseases across the board. Keywords: Periodontitis, Smoking, Periodontal health, Assessment